Mindfulness based feminist therapy: The intermingling edges of self-compassion and social justice. Issue 1 (2nd January 2016) - Crowder, Rachael
ABSTRACT: Survivors of intimate partner violence (IPV) often have trouble regaining a lost sense of self, even after years of 'good' feminist therapy. Both postmodern feminism and Buddhist philosophy have common ideas about the constructed nature and fluidity of the self, and feminist and Buddhist ontologies can inform each other—the former on the nature of subjectivity under oppression, the latter on how to relate differently to the self by not identifying with our stories as who we are. Therefore, one might assume that mindfulness-based approaches might be helpful with this problem. However, social justice values that feminists and social workers prize seem absent in mindfulness approaches that appear to be individual-focused and politically passive. This article argues that feminism and mindfulness have points of congruence as well as much to offer each other where they diverge, and it presents exploratory research investigating the role of mindfulness and self-compassion on reconstructing a sense of self and agency in survivors of IPV by comparing outcomes of a community-based feminist group and a mindfulness-based group. The findings provide a glimpse into the strengths of each approach and suggest some benefit in weaving these into a mindfulness based feminist therapy for survivors of IPV.